2021
DOI: 10.15294/aaj.v10i1.44516
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Profitability, Liquidity, and Asset Structure on Capital Structure with Firm Size as Moderating Variable

Abstract: The purpose of this research is to analyze the effect of profitability, liquidity, and asset structure on capital structure with firm size as a moderating variable. The population of this study was all property and real estate companies listed on the Indonesian Stock Exchange (IDX) from 2014-2016. The number of samples used was 39 companies with the audit of analysis of 117. This study used secondary data taken from the annual financial statements. The method of data analysis was descriptive analysis and Moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
3
21
0
1
Order By: Relevance
“…With the existence of reduced short-term debt, it can result in a decrease in the proportion of the capital structure. In addition, there are similar results from several studies, namely Septiani and Suaryana (2018), Dewi and Fachrurrozie (2021) and Gunadhi and Putra (2019). H4: Liquidity has a negative effect on Capital Structure…”
Section: Effect Of Liquidity On Capital Structuresupporting
confidence: 83%
“…With the existence of reduced short-term debt, it can result in a decrease in the proportion of the capital structure. In addition, there are similar results from several studies, namely Septiani and Suaryana (2018), Dewi and Fachrurrozie (2021) and Gunadhi and Putra (2019). H4: Liquidity has a negative effect on Capital Structure…”
Section: Effect Of Liquidity On Capital Structuresupporting
confidence: 83%
“…In addition, it is feared that companies with high debt will not be able to pay their debts according to the specified time and it will be more difficult for companies to earn high profits. This statement is in accordance with the results of research conducted byDewi & Fachrurrozie (2021), where leverage has a negative effect on earnings quality.On the other hand, research conducted byWati and Putra (2017) shows that leverage has no effect on earnings quality. In the research it was said that although the level of leverage and company risk is high, it does not mean that the company's earnings quality are not good because the company can still improve the quality of its earnings even though it has a high debt to asset ratio (DAR) if the company can manage debt efficiently, and has more conservative inventory and credit sales management.Based on the argument above, the research hypothesis can be formulated as follows: H1: Leverage affects earnings quality.…”
supporting
confidence: 92%
“…Balios et al (2016) also found that the relation between asset structure and leverage of the company is negative. Similarly, the asset structure was found as the factor negatively affecting the capital structure in the paper of Dewi and Fachrurrozie (2021). The opposite results were reported by Kenourgios et al (2020), who found tangible assets structure ratio negatively impacting the level of leverage.…”
Section: Literature Reviewmentioning
confidence: 77%